Architectural Features of the Church of St. Demetrius in Veles: An Analysis of Recent Discoveries - Maltseva, Svetlana V.; Nikolovski , Darko (Actual Problems of Theory and History of Art, 2024)
The article is devoted to an in-depth study of the architectural features of the Church of St. Demetrius the Great Martyr in Veles. For an extended period, there was a lack of available information regarding the date of construction of the church and its history during the Middle Ages. The first to undertake a study of the church was the Yugoslav historian of architecture J. Bošković. In the absence of any information regarding the history of the church, he attributed its architectural solution to the second half of the 14th century. As a result, the Church of St. Demetrius in Veles was included in the primary reviews on the Balkan architecture, and was considered to be in a similar style to the churches of Serbia. An alternative viewpoint, which posits the possibility of categorizing the church in Veles within the context of early Paleologian architecture of the 13th century, was initially presented in the thesis of the Macedonian historian of architecture Sasho Korunovski. During the restoration work conducted between 2018 and 2022 by a team of specialists from the NI National Conservation Center in Skopje, the original murals were discovered and cleared of lime plaster in the interior of the narthex, on its eastern and northern walls. The newly discovered fragments of murals on the eastern wall of the northeastern corner of the narthex have revealed a ktitor’s composition depicting a large figure holding a model of the church in his hand. A lengthy dedicatory inscription accompanies the ktitorial portrait. Despite the considerable damage, the majority of the text could be deciphered. The date of construction and the name of the ktitor have been identified. Once the dating was clarified, it became possible to undertake a more detailed analysis of the architectural features of the church in the context of the artistic traditions of the era in which it was constructed.This work is supported by the Russian Science Foundation (grant 20-18-00294-P) and done at the Research Institute of Theory and History of Architecture and Town Planning — branch of the Central Research and Project Institute of the Construction Ministry of Russia.
Keywords: Veles; Paleologian architecture; architecture of Northern Macedonia; Architecture of Epirus; Archbishopric of Ohrid; Kotanitzes Tornikios